Fast pyrolysis of hardwood residues using a fixed bed drop-type pyrolyzer - Mazlan, M.A.F. (Elsevier Ltd, 2015)
In this research, rubber wood sawdust (RWS) and Meranti wood sawdust (MWS) were pyrolyzed in a fixed bed drop-type pyrolyzer under an inert condition. The first part of the study is to determine the influence of pyrolysis temperature (450, 500, 550, 600, 650 °C) on the yield of pyrolysis products. Pyrolysis of these different residues generate an almost identical maximum amount of bio-oil close to 33 wt., but at different maximum temperature (550 °C for pyrolysis of RWS and 600 °C for pyrolysis of MWS). To evaluate the effect of biomass type on the composition and characterization of pyrolysis products, the second part involves the analyses of pyrolysis products from the maximum pyrolysis temperature. Acetic acid, tetrahydrofuran, and benzene were the main bio-oil components. The bio-oil contained high percentage of oxygen and hydrogen, indicating high water content in the bio-oil. High amount of water in bio-oil significantly reduced its calorific value. Under extensive heating, particle size of the bio-char from SEM images decreased due to breakage and shrinkage mechanisms. The major components of non-condensable gases were CO and CO2. © 2015 Elsevier Ltd. All rights reserved.